The Use of Technology in Education to Enhance Student Engagement in 5th Grade SD Negeri 3 Sabang - Wulan Sulastri Asmita (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review aims to examine the critical role of technology in educational contexts, particularly its influence on enhancing student engagement among 5th-grade students at SD Negeri 3 Sabang. In an era where digital advancements are rapidly transforming various aspects of society, the integration of technology in classrooms has become increasingly essential. This review synthesizes existing research findings to provide a comprehensive understanding of how various technological tools—such as interactive whiteboards, educational software, online collaborative platforms, and mobile applications—can be effectively utilized to create a more dynamic and engaging learning environment. The review begins by defining student engagement and its significance in the learning process, emphasizing that engaged students are more likely to participate actively, demonstrate improved academic performance, and develop a love for learning. It explores how the incorporation of technology not only captures students' interest but also facilitates differentiated instruction that caters to diverse learning styles. By analyzing case studies and empirical research, this review identifies the most effective technological strategies that have been implemented in classrooms and evaluates their outcomes in terms of student participation and motivation. Furthermore, the literature review addresses potential challenges faced by educators in adopting technology, including issues related to access, teacher training, and the necessity of balancing screen time with traditional teaching methods. It highlights the importance of ongoing professional development for teachers to effectively integrate technology into their curriculum. The study concludes with practical recommendations for educators and school administrators, emphasizing the need for a well-structured technology integration plan that aligns with curriculum goals and supports student engagement. Overall, this literature review contributes to the growing body of knowledge on educational technology by providing insights and evidence-based strategies that can enhance student engagement. It underscores the transformative potential of technology in education and encourages further research to explore innovative practices that continue to improve learning experiences for students